Random fields with independent increments - Katkauskaitė, A. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Каткаускайте. Случайные поля с независимыми приращениямиA. Katkauskaitė. Atsitiktiniai laukai su nepriklausomaisiais pokyčiais